Sejarah dan Perkembangan Muhammadiyah di Desa Takerharjo Solokuro Lamongan 1966-2017 - Khofifatul Qolbi (Qurthuba: The Journal of History and Islamic Civilization, 2019)
Abstract: This article examines the history and development of Muhammadiyah in the village of Takerharjo Lamongan. The focus of the research discussed in this thesis are (1) What is the history of the founding of Muhammadiyah in the village of Takerharjo Solokuro Lamongan. (2) How was the development of Muhammadiyah in the village of Takerharjo Solokuro Lamongan in 1966-2017. (3) What are the supporting and inhibiting factors for the establishment and development of Muhammadiyah in the village of Takerharjo, Solokuro Lamongan. The method of writing history used by the author is to use several steps, namely the method of historical science by collecting archives related to the intended discussion, verification, interpretation and writing of history. The theory taken from this research is the modernization theory put forward by Max Weber. The results of this study conclude that (1) The history of the founding of Muhammadiyah in Takerharjo in 1966-2017 which was chaired by Mr. H.Syakur. Initially it was due to the condition of the people who still followed traditions that had no demands on Islamic teachings and a lack of understanding and experience of religion Islam in the practice of daily life. (2) The development of Muhammadiyah in Takerharjo experienced a lot of progress which was quite rapid in its early emergence and was quite good in terms of the members' charitable efforts and their religious activities from 1966-2017. (3). There were supporting and inhibiting factors at the time of the founding and development of Muhammadiyah in the village of Takerharjo Solokuro Lamongan in 1966-2017. Keywords: history, Muhammadiyah, Takerharjo